Дискурсні практики медіа-сфери Росії: синтез двох ідеологій чи розмивання орієнтирів - Козиряцька, Світлана Анатоліївна (Кам'янець-Подільський : Аксіома, 2016)
У статті обґрунтовано, що дискурсні практики медіа-сфери Росії є ідеологічно зумовленими, а не хаотичними й ситуативними, що спонукає ЗМІ вдаватися до архетипів, політичних міфів, стереотипів як інструментів медіа-технологій, використовуючи їх у контексті ментальності як важливої етнопсихологічної ознаки нації. Розглянуто провідні ментальні риси, на які орієнтуються російські медіа, транслюючи нову радянсько-імперську ідеологію. Визначено архетипи, які найчастіше репрезентовані в медіа-текстах та які сприймаються як знайомий контекст, стимулюючи ефект довіри до інформаційного продукту, що полегшує вплив на свідомість. З’ясовано роль міфів та міфологем у контексті формування нової ідеології. The article deals with the possible direction of the vectors of Russian media orientation: development and promotion of new hybrid ideology, based on a synthesis of two paradigms – imperial and Soviet, or destruction of world’s view and erosion benchmarks which facilitate the usage of the manipulative technologies. It is proved, that discursive practices of Russian media sphere is still remain ideologically conditioned, which encourages the media to use archetypes, political myths, stereotypes as a tool for designing new reality and promoting the right ideology. The research is carried out in the coordinate system «archetype, myth, stereotype-mentality» because these «values» are interrelated and serve as means of media exposure in mass media (Myths, archetypes, stereotypes), and as a filter through which perceived media message (myths, stereotypes, mentality) and as a set of conditions for which the communicator, is oriented to provide media effect (archetypes, myths, stereotypes, mentality). It is important to understand new imperial and Soviet ideology distributed by media, the following mental traits as a willingness to delegate responsibility, a tendency to obedience, collective subordination; dominance of emotion over rationality and therefore religion (as communicators (TV or radio) the priests are transferred ideologically oriented messages, providing the right media effect due to high personal trust of recipients). Russian media is focused on the use of archetypes as Mother Earth (social image of the «Russia-mother») which is successfully used by the media to awaken people’s solidarity in facing «internal and external enemies»; Warrior, who also evokes the original archetype and focuses on awakening of cohesion; the father (the hero, the leader) that creates Putin personality cult; archetype «hero criminal» (Stalin, Ivan Grozny), emphasizing the necessity of «strict but wise ruler». Among the political myths are used by Russian media the revival of the concept of «Moscow – the Third Rome» and therefore is spread the myth of «great spiritual mission» of Russia as the successor to the Byzantine Empire; revival of the idea of «Russian World», «Russian land»; mythology leader, «father of the nation» mythology pretentious enemy and fight him.
Keywords: журналістика; соціальні комунікації; медіа-сфера; стереотип; міф; архетип; менталітет